HISTOLOGICAL PATTEREN OF NEPHROTIC SYNDROME IN ELDERLY PATIENTS - Akhtar, Sultan Zaffar; Ali, Akbar (Journal of Ayub Medical College Abbottabad, 2008)
Background: Renal biopsy is a safe and informative technique that has played a key role in the evolution of nephrology as a specialty. This cross-sectional descriptive study was aimed to study the histological pattern of nephrotic syndrome in elderly patients. Methods: This study was conducted from January 1998 to December 2005 (8 Years) in the Department of Nephrology, Govt. Lady Reading Hospital, Peshawar, Pakistan. We performed renal biopsy in 153 patients aged 60 years and above, admitted with nephrotic syndrome-proteinuria with protein >3 gm/24 hours with or without oedema, hypoalbuminemia, hyperlipidemia, acute nephritic syndrome-red blood cell casts or dysmorphic red cells on urine microscopy, temporally associated with acute renal failure with or without new onset hypertension, acute renal failure-sudden decline in renal functions developing in days to weeks causing retention of nitrogenous wastes and rapidly progressive renal failure-sub acute decline in renal functions developing over weeks to months. Results: Significant differences in the histological pattern are noticed when compared with the studies of the other centres. Minimal Change Disease (MCD) was the commonest histological pattern (40%), followed by Membranous Nephropathy (21%), Crescentic Nephritis (19.6%), Focal Segmental Glomerulosclerosis (FSGS) (6.5%), Hypertensive Nephropathy (5.8%), Messangiocapillary Glomerulonephritis (MCGN) (3.9%) and Diffuse Proliferative Glomerulonephritis (DPGN) (3.2%). Keywords: Renal Biopsy, Glomerulonephritis, Minimal Change Disease, Membranous Nephropathy, Crescentic Nephritis, Focal Segmental Glomerulosclerosis, Hypertensive Nephropathy, Messangiocapillary Glomerulonephritis, Diffuse Proliferative Glomerulonephritis